Produção de ácidos orgânicos por cepas leveduras assimiladoras de xilose - Monteiro, Diego Alves [UNESP] (2015)
The hydrolysis of polysaccharides from lignocellulosic biomass releases high quantity of pentoses, whose fermentation to ethanol could be a complement that obtained by fermentation of glucose derived from cellulose saccharification (2G ethanol). However, despite efforts in research, this is still a technology in development. Moreover, the use of pentoses as a substrate for obtaining value-added bioproducts is an alternative to ethanol and an economically viable route. This project proposes the study of xylose assimilating yeast focused on metabolites generated from the use of xylose as carbon source. Pichia kluyveri G1.1; Hanceniaspora sp. G4.1; Hanceniaspora sp. G7.1; Candida oleophila G10.1; Metschnikowia koreensis G18 were selected for this study based on their potential of assimilation of xylose studied in previous work. The data showed that Hanceniaspora sp. G4.1, Hanceniaspora sp. G7.1 and C. oleophila G10.1 consumed 100% of xylose from the culture medium in 120 h. M. koreensis G18 consumed approximately 70% in 96 h and P. kluyveri G1.1 was the strain that presented the lowest xylose consumption rate ( 50% in 120 h). Qualitative evaluation of the organic acids secreted by strains in these cultures revealed the presence of oxalic, citric, maleic, tartaric, malic, pyruvic, lactic, fumaric, acetic, propionic, isobutyric, and butyric acid. In cultivation using culture media with different initial pH values and concentrations of xylose it was observed that these factors influence the production of organic acids by M. koreensis G18, however, were not significant for other yeasts